Active basement uplift of Sierra Pie de Palo (Northwestern Argentina): Rates and inception from10Be cosmogenic nuclide concentrations. Issue 6 (6th June 2015) - Siame, Lionel L.; Sébrier, Michel; Bellier, Olivier; Bourlès, Didier; Costa, Carlos; Ahumada, Emilio A.; Gardini, Carlos E.; Cisneros, Hector
Abstract Quaternary tectonic and denudation rates are investigated for an actively growing basement anticline: the Sierra Pie de Palo range, which belongs to the Andean foreland of Northwestern Argentina (28°S–33°S). In this study, a detailed morphometric analysis of the topography is combined with in situ‐produced cosmogenic10Be concentrations measured in (1) surface boulders abandoned on alluvial terraces affected by fault activity (along the north bounding fault) and growth of the basement fold (along the southeastern border), (2) bedrock outcrops corresponding to an exhumed and folded, regional erosion surface, and (3) fluvial sediments sampled at the outlets of several watersheds. Along the eastern and northern borders of the range, incision and uplift rates have been estimated at approximately 0.5 and 1 mm/yr when integrated on Holocene and Pleistocene time scales, in close agreement with both long‐term (structural and basin evolution data) and short‐term (GPS‐derived velocity field) analyses. Cosmogenic‐derived denudation and uplift rates combined with geomorphic characteristics of watersheds and river channels allows estimating the onset of the uplift at 4–6 Ma, followed by a more recent period of topographic rejuvenation at roughly 1–2 Ma, probably synchronous with steepening of the eastern and northern flanks of the anticline.